Implementation of Good Corporate Governance in Creating Bank Performance Sustainability Using Partial Least Square Method - Agus, Supriyatna; Moch Dudih, Sugiharto; Erwin, Yulianto; Neneng, Hayati (INTI International University, 2022)
Performance is an achievement picture of activity implementation in realizing the company's goals. An important goal in the establishment of a company is to improve the welfare of its owners or shareholders by maximizing shareholder wealth through increasing the company's value. Business performance is needed and important for the company. This certainly will be a distinct advantage for a company if it has good business performance. PT. Bank Pembangunan Daerah Jawa Barat dan Banten, Tbk. with the call name bank BJB is one of the BUMD that is engaged in the banking industry sector with category of BUKU 3. The research analysis unit is conducted at branch offices throughout all the bank BJB network of service and operations. In the last five years, the trend of bank BJB performance still tends to fluctuate, especially in the period 2013-2014 and 2016-2017 which has decreased. This can be seen in the balanced scorecard parameters of each branch office performance index for the 2014-2018 period. One reason for the decline in bank BJB performance is the poor implementation of Good Corporate Governance (GCG). The phenomenon of bank BJB performance fluctuated in line with the GCG ranking statistics issued by the LPPI where bank BJB's GCG rating was above the average rating of the national banking industry's GCG standard. The current GCG implementation is mostly carried out at the corporate level and lacks of optimal GCG implementation at the business, operational and functional levels, in this case, is the branch office. The modeling of the research framework is designed using the Partial Least Square model which is a method for estimating the path model that uses latent extract with multiple indicators. Based on the phenomenon that occurs in bank BJB, the research framework that will be explored is testing the hypotheses related to the description of the external environment, internal environment, and corporate value towards the GCG implementation in creating bank performance sustainability.